A transcriptomic approach to pigs at weaning: a role for Saccharomyces cerevisiae boulardii? - Watts, Oliver (2018)
Weaning is a stressful period in the early life of a pig. This stress manifests as immediate weight loss coinciding with increases in intestinal transepithelial resistance. This study aims to identify the transcriptional differences in the colon between suckling and weaned animals over this period using RNA-seq. This approach identified the maximal transcriptional differences at one-day post-weaning with 353 transcripts differentially expressed compared to 78 and three transcripts at four and fourteen days post weaning respectively (q<0.1, FC>2). This work identified increased transcription of pro-inflammatory cytokine genes including IL1A (FC=2.63) and IL1B2 (FC = 2.98) in the colon of weaned animals at one-day post weaning, suggesting activation of the immune system. The same time points at one, four and 14 days post weaning was used to assess the transcriptional effect of supplementation with probiotic Saccharomyces cerevisiae boulardii (4.43 Log10 CFU per day from seven days of age) on the colon. A distinct effect of probiotic yeast supplementation on transcription in the colon was identified in both weaned and suckling pigs. One, 77 and one transcripts were affected by the probiotic in weaned animals at the three time points respectively compared to 197, six and two in suckling animals. However, evidence of an anti-inflammatory effect (including increased expression of IL10, FC = 2.88) was identified in weaned animals at four days post-weaning. The clear distinction between differential expression in weaned and suckling animals suggests that the transcriptional effect of Saccharomyces cerevisiae boulardii supplementation may depend on the physiological state of the host. These differences may be due to the interaction of the probiotic with the host immune system as a result of weaning related bowel disruption.